تأثير التسميد ببعض مستخلصات الطحالب البحرية في نمو وإنتاج ونوعية ثمار صنف التفاح Golden delicious - ديب, علي; خربوتلي, رشيد; منان, محمد (Latakia University Journal -Biological Sciences Series, 2018)
This research was conducted on twenty four year’s old cv “Golden delicious” Apple trees grafted on Malus domestica rootstock and planted 5x5 m in Aleppo, during 2015. marine algae extracts were used with three concentrations (0.25, 0.5, 0.75) g/L, ml/L, with application soil fertilization. It can summarize the most important results as following: Treatment with Swc3sf have improved the length of shoots (33.72 cm), leaf area (36.81 cm2) and increasing ratio of trunk was (1.59 %) comparing with the control (1.11%, 25.28cm2, 25.10cm). Treatment with marine algae extract Swb3sf reduced the fruit drop ratio in June to 7.20% compared with 14.15% in the control and setting ratio were increased (49.13%) and fruiting average was (24.29%) and best production high (175.81 kg/tree) compared with the control (130.51 kg/tree, 38.49%،12.51% ) respectively. These extracts have improved the chemical characteristics of fruits comparing with the control. The third treatment(0.75 g/l) of Swa3sf had improvement the physical properties of fruits, where the Weight of fruit had reached (163.92 g) and (169.81cm3), comparing with the control (130.82g, 136.72 cm3) respectively. نفذ البحث في محافظة حلب على أشجار التفاح صنف Golden delicious بعمر 24 عاماً، مطعمة على أصل Malus domestica وبمسافات زراعة 5X5 متر، خلال موسم النمو لعام2015 ، وذلك باستخدام مستخلصات الطحالب البحرية بعدة تراكيز ml/l،g/l ( 0.75 ،0.5 ،0.25), مع تسميد أرضي أساس. وفيما يلي أهم النتائج المتحصل عليها: حسنت المعاملة Swc3sf من متوسط طول الطرد (33.72 سم) و المسطح الورقي (36.81 سم2) ونسبة الزيادة في محيط الساق (1.59%)، مقارنة بالشاهد (25.10 سم، 25.28 سم2، 1.11 %) على التوالي. خفضت معاملة مستخلص الطحالب البحرية Swb3sf من نسبة تساقط الثمار في حزيران إلى 7.20% مقابل 14.15% بالشاهد. و زادت من عقد الثمار(49.13%)، ومعامل الإثمار( 24.29%)، وأعلى إنتاجية ( 175.81 كغ/شجرة) مقابل (38.49%،12.51%، 130.51 كغ /شجرة) على التوالي في معاملة الشاهد. وحسنت من الصفات الكيميائية للثمار مقارنة بالشاهد. حسنت المعاملة Swa3sf بتركيز (g/l 0.75) من الصفات الفيزيائية للثمار، إذ وصل وزن الثمرة الى (163.92 غ)، وحجمها الى (169.81 سم3)، بينما كانت في الشاهد (130.82 غ، 136.72 سم3) على التوالي.